Immunomodulatory Effects of Diterpenes and Their Derivatives Through NLRP3 Inflammasome Pathway: A Review - Islam, Muhammad Torequl; Bardaweel, Sanaa K.; Mubarak, Mohammad S.; Koch, Wojciech; Gaweł-Beben, Katarzyna; Antosiewicz, Beata; Sharifi-Rad, Javad (Frontiers in Immunology, 2020)
Nucleotide-binding oligomerization domain-like receptor family pyrin domain-containing proteins (NLRPs) inflammasome are involved in the molecular pathogenesis of numerous diseases, including insulin resistance, obesity, inflammation, and neurological disorders. Diterpenes are in the spotlight due to their promising therapeutic effects. This review sketches a current scenario of diterpenes acting through NLRPs-associated pathways with anti-inflammatory effects. For this, a literature survey on the subject has been undertaken using known databases such as the American Chemical Society, Clinicaltrials.gov, Google Scholar, PubMed, Scopus, Science Direct, and Web of Science. Findings from the aforementioned databases suggest that diterpenes can exert anti-inflammatory effects via NLRPs-related pathways. In conclusion, diterpenes and their derivatives could be promising compounds for the treatment of NLRPs-mediated diseases and disorders.